2020
DOI: 10.1007/s10815-020-01693-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution 1H-NMR spectroscopy indicates variations in metabolomics profile of follicular fluid from women with advanced maternal age

Abstract: Aim To reveal whether there are differences in follicular fluid metabolomics profile of women with advanced maternal age (AMA). Method The group with advanced maternal age includes 23 patients above the age of 40, and the control group includes 31 patients aged between 25 and 35 years and AMH values above 1.1 ng/mL with no low ovarian response history. A single follicular fluid sample from a MII oocyte obtained during the oocyte pick-up procedure was analyzed with high-resolution 1 H-NMR (nuclear magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Our study provides a phenotypical characterization of the T-cell subsets that are defective at the maternal-fetal interface of advanced-age mothers. However, it is important to note that aging of the reproductive organs [158][159][160][161][162], as well as other pathological processes [163][164][165][166], must be considered when studying the mechanisms whereby advanced maternal age causes prolonged labor. It is worth mentioning that the pathological processes involved in prolonged labor are confined to the intrauterine space, given that the alterations in T-cell subsets were not observed in the lymphatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a phenotypical characterization of the T-cell subsets that are defective at the maternal-fetal interface of advanced-age mothers. However, it is important to note that aging of the reproductive organs [158][159][160][161][162], as well as other pathological processes [163][164][165][166], must be considered when studying the mechanisms whereby advanced maternal age causes prolonged labor. It is worth mentioning that the pathological processes involved in prolonged labor are confined to the intrauterine space, given that the alterations in T-cell subsets were not observed in the lymphatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…There are no unanimous findings in previous studies on the concentrations of these energy-linked metabolites in FF of IF compared to those of CTRL. Results indicating either normal glucose and higher lactate [5], higher glucose and lower lactate [16], higher glucose and higher lactate [27], lower glucose and higher lactate [28][29][30], lower glucose and lower lactate [9], have been published in the last years. It is worth underlining that most of the aforementioned data have been carried out by selecting one specific category of female infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Follicles, CC and oocytes differentially express specific pattern of genes as they age, affecting oocyte maturation and, possibly, altering the developmental competence of the maturing oocyte. Several studies have identified non-invasive markers to predict oocyte quality, embryo development and pregnancy outcomes by analyzing the transcriptome of human CCs [17][18][19][20][21], including comparisons between CC from young and older women [22][23][24], Recently, alterations in CC response to the follicular microenvironment have been described in AMA [25][26]. One such pathway is the hypoxia-dependent response, which controls the cell metabolic and oxidative state.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%